Prolonged Use of Proton Pump Inhibitors, but Not Histamine-2 Receptor Antagonists, Is Associated With Lower Bone Mineral Density in Males Aged Over 70 - Gao, Shihua; Song, Wenting; Lin, Tianye; Chen, Wenhuan; He, Wei; Wei, Qiushi; Li, Ziqi (Frontiers in Medicine, 2021)
Aims: The association of acid suppressants use with bone mineral density (BMD) is still unclear, especially in older adult with prolonged use of proton pump inhibitors (PPIs) or histamine-2 receptor antagonists (H2RAs). In this study, our aim was to investigate the association between PPI or H2RA use and BMD in general US older adults. Methods: We conducted a cross-sectional study on a sample from National Health and Nutrition Examination Survey. Association between long-term use of PPIs or H2RAs and lumber spine BMD in elderly was evaluated using weighted multivariate linear regression models. Sensitive and subgroup analysis were also performed in this study. Results: Long-term PPI use is correlated with lower lumber spine BMD in our multivariable regression model after adjusting for known confounding factors. Further analysis showed PPI use with a duration over 1 year was negatively associated with lumber spine BMD in male, elderly aged over 70 years and white elderly. There is no significant association between long-term H2RA use and lumber spine BMD. Conclusions: Our results indicated that the association between long-term use of PPI and lumber spine BMD differed by gender. Long term use of PPIs would reduce lumber spine BMD in older men, while H2RA use is not significantly linked with lumber spine BMD. In patients that are at high risk of bone loss should shortened the duration of PPI use (< 1 year) or use H2RAs as alternative if possible.